Affiblot: a dot blot-based screening device for selection of reliable antibodies. Issue 35 (23rd August 2021) - Svobodova, Zuzana; Novotny, Jakub; Ospalkova, Barbora; Slovakova, Marcela; Bilkova, Zuzana; Foret, Frantisek
Abstract : A report on a palm-sized dot blot-based device that allows simultaneous semi-quantitative comparison of up to five antibodies from different suppliers regarding their affinity/avidity, cross-reactivity, and batch-to-batch reliability. Abstract : The key factor in the development of antibody-based assays is to find an antibody that has an appropriate affinity, high specificity, and low cross-reactivity. However, this task is not easy to carry out since the research antibodies on the market may suffer from low specificity and reproducibility. Here, we report on a palm-sized dot blot-based device, called the affiblot, that has a specially designed lid that allows simultaneous semi-quantitative comparison of up to five antibodies from different suppliers regarding their affinity/avidity, cross-reactivity, and batch-to-batch reliability. The only required peripheral equipment is a vacuum pump, a camera, and densitometry software. The affiblot device was tested for its functionality and its measurements were compared against those obtained by standard dot blot and ELISA. The benefit over these methods, when various antibodies are evaluated, is in its simplicity. It allows easy antigen deposition, fast application and the discarding of the solutions, a compact undivided membrane, and therefore significant decrease of labor. The device was tested with specific anti-ApoE, anti-EpCAM, anti- Salmonella, anti- E. coli, and anti- Listeria antibodies from different suppliers. Their properties were compared for their ability to interact specifically with antigen and/or non-target structures and the best-suited antibody for the intended application was identified.